Staufen‐2 functions as a cofactor for enhanced Rev‐mediated nucleocytoplasmic trafficking of HIV‐1 genomic RNA via the CRM1 pathway. (19th June 2022) - Balakrishnan, Kannan; Munusami, Punnagai; Mohareer, Krishnaveni; Priyakumar, U. Deva; Banerjee, Atoshi; Luedde, Tom; Mande, Shekhar C.; Münk, Carsten; Banerjee, Sharmistha
Abstract : Nucleocytoplasmic shuttling of viral elements, supported by several host factors, is essential for the replication of the human immunodeficiency virus (HIV). HIV‐1 uses a nuclear RNA export pathway mediated by viral protein Rev to transport its Rev response element (RRE)‐containing partially spliced and unspliced transcripts aided by the host nuclear RNA export protein CRM1. The factor(s) interacting with the CRM1‐Rev complex are potential antiretroviral target(s) and could serve as a retroviral model system to study nuclear export machinery adapted by these viruses. We earlier reported that cellular Staufen‐2 interacts with Rev, facilitating viral‐RNA export. Here, we identified the formation of a complex between Staufen‐2, CRM1 and Rev. Molecular docking and simulations mapped the interacting residues in the RNA‐binding Domain 4 of Staufen‐2 as R336 and R337, which were experimentally verified to be critical for interactions among Staufen‐2, CRM1 and Rev by mutational analysis. Staufen‐2 mutants defective in interaction with CRM1 or Rev failed to supplement the Rev‐RNA export activity and viral production, demonstrating the importance of these interactions. Rev‐dependent reporter assays and proviral DNA‐construct transfection‐based studies in Staufen‐2 knockout cells in the presence of leptomycin‐B (LMB) revealed a significant reduction in CRM1‐mediated Rev‐dependent RNA export with decreased virus production as compared to Staufen‐2 knockout background or LMB treatment alone, suggesting the relevance of these interactions in augmenting RNA export activity of Rev. Our observations provide further insights into the mechanistic intricacies of unspliced viral‐RNA export to the cytoplasm and support the notion that abrogating such interactions can reduce HIV‐1 proliferation. Abstract : HIV‐1 amplification in the host is dependent on the successful export of unspliced/partially spliced RRE‐RNA from the host nucleus to the cytoplasm and is one of the rate‐limiting steps in HIV‐1 lifecycle. This export of RRE‐RNA is mediated by HIV‐1 Rev that interacts with several host proteins. The study showed that interactions between HIV‐1 Rev and host RNA‐binding proteins, Staufen‐2 and CRM1, augmented Rev‐mediated RRE‐RNA export and viral titers.